2020
DOI: 10.1155/2020/9578484
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressive Roles and Prognostic Values of STEAP Family Members in Breast Cancer

Abstract: Objective. To investigate the expression patterns and prognostic values of STEAP family members in the occurrence and development of breast cancer. Materials and Methods. The Human Protein Atlas was used to analyze the expression level of STEAPs in human normal tissues and malignant tumors. ONCOMINE datasets were analyzed for the comparison of the STEAPs levels between malignant cancers and corresponding normal tissues. Kaplan-Meier plotter was used to analyze the prognostic value of STEAPs in breast cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…STEAP2 has been reported to be downregulated in breast cancer [21]. STEAP2 overexpression signi cantly inhibited proliferation and clonogenesis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…STEAP2 has been reported to be downregulated in breast cancer [21]. STEAP2 overexpression signi cantly inhibited proliferation and clonogenesis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of STEAP2 can inhibit the invasion and metastasis of breast cancer cells by inhibiting epithelial-mesenchymal transformation by affecting transcription factors [14]. In contrast, STEAP2 is signi cantly overexpressed in prostate cancer, and its overexpression promotes the proliferation, migration, and invasion of tumor cells [21]. Activation of the ERK pathway by STEAP2 leads to partial stagnation of the g0-G1 cell cycle in cancer cells, increasing proliferation and tumor development [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STEAP family members are relatively new proteins and their potential as prognostic biomarkers have been demonstrated in breast cancer (56), glioblastoma (57,58), Ewing tumors (30), skin disorders (59) and prostate cancer (7). A recent study that explored the use of STEAP proteins as possible prognostic indicators in prostate cancer showed that only STEAP4 was overexpressed, and significantly associated with relapse (7).…”
Section: Prognostic Value Of Steap Proteins In Prostate Carcinomamentioning
confidence: 99%
“…It is a 339 amino acid transmembrane protein implicated in cell adhesion, regulation of reactive oxygen species levels, and acts as an ion channel or transporter for cell–cell communication [ 24 ]. STEAP1 expression is highly upregulated in several cancers, including prostate, bladder, pancreas, ovary, gastrointestinal tract, cervix, and testicular cancer, as well as ES [ 25 , 26 , 27 , 28 , 29 ]. In the case of ES, STEAP1 is a direct transcriptional target of EWSFLI1 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%